SY 17-2 INFLAMMATION, IMMUNITY AND HYPERTENSION. (September 2016) - Harrison, David
Abstract : Hypertension remains an enormous health care burden that affects one third of the population. Despite its prevalence the cause of most cases of hypertension remains unknown. Our laboratory has defined a novel mechanism for hypertension involving adaptive immunity. We found that mice lacking lymphocytes (RAG-1 -/- mice) develop blunted hypertensive responses to a variety of stimuli including chronic angiotensin II infusion, DOCA-salt challenge and norepinephrine infusion. Adoptive transfer of T cells, but not B cells, restores the hypertensive responses to these stimuli. Hypertension is associated with the infiltration of T cells into the kidney and vasculature, where they release cytokines, including IFN-g, IL-17A, and TNFa, which promote sodium retention, vasoconstriction and oxidative injury. Recently, we have found that angiotensin II has striking effects on dendritic cells (DCs), promoting their propensity to activate T cells. Our data indicate that angiotensin II infusion increases DC superoxide production by 5-fold and causes a striking accumulation isoketals, oxidized products of arachidonic acid in these cells. These form covalent bonds to lysines of proteins and these modified proteins become immunogenic. Several isoketal scavengers, including 2-hydroxybenzylamine (2-HOBA) prevent DC activation, the ability of DCs to stimulate T cell proliferation and prevent hypertension. This is most prevalent in monocyte-derived DCs that are CD11c/CD11b/MHCII positive. The precise mechanism for formation of these cells is under investigation. A major impetus for immune cell activation seems to be increased sympathetic outflow, stimulated by the central actions of angiotensin II. By lesioning the AV3 V region of the forebrain of mice or inactivating the NADPH oxidase in the subfornical organ using Cre Lox technology, we have prevented the central actions of angiotensin II and found that this inhibits both T cell activation and hypertension. Renal denervation likewise prevents activation of DCs in the kidney and the accumulation of activated DCs in the spleen. Thus, the kidney seems to be a major site of DC activation in hypertension. In summary, we have identified a new mechanism underlying hypertension and a potential new therapy for this common and yet difficult to manage disease.